1984
DOI: 10.1159/000284079
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Factors in Panic Disorder

Abstract: Panic disorder patients were compared with normal subjects during intravenous infusion of sodium lactate, isoproterenol, and placebo. Panic attacks meeting the criteria of the Diagnostic and Statistical Manual, vol. 3 [American Psychiatric Association, 1980] occurred during all three conditions in patients and during the lactate and isoproterenol infusions in normals. Patients had significantly higher average levels of skin conductance, heart rate and state anxiety, and significantly lower finger temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
3

Year Published

1984
1984
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 15 publications
0
25
1
3
Order By: Relevance
“…Finally, we confirmed the finding of Neophytou et al (2000) that ultrasound induces c-Fos expression in the dorsal regions of the PAG and the amygdala, two regions frequently associated with human panic disorder (reviewed in Graeff and Del-Ben 2008), and demonstrated that these expressions were differentially modulated by the anxiolytic with panicolytic properties diazepam and the preclinical anxiolytic Ro 64-6198. The observed increases in heart rate and core body temperature are known autonomic symptoms of human panic attacks (Freedman et al 1984;Cameron et al 1987;DSM IV 2003) and animal panic reactions (Gray and McNaughton 2000). However, since tachycardia and hyperthermia are common features of aversive autonomic activation, they are considered as more general autonomic markers of classical "fight and flight" reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we confirmed the finding of Neophytou et al (2000) that ultrasound induces c-Fos expression in the dorsal regions of the PAG and the amygdala, two regions frequently associated with human panic disorder (reviewed in Graeff and Del-Ben 2008), and demonstrated that these expressions were differentially modulated by the anxiolytic with panicolytic properties diazepam and the preclinical anxiolytic Ro 64-6198. The observed increases in heart rate and core body temperature are known autonomic symptoms of human panic attacks (Freedman et al 1984;Cameron et al 1987;DSM IV 2003) and animal panic reactions (Gray and McNaughton 2000). However, since tachycardia and hyperthermia are common features of aversive autonomic activation, they are considered as more general autonomic markers of classical "fight and flight" reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the State Anxiety Inventory ratings are to be reported separately [16,32], The Hamilton Anxiety Scale scores for the panic disorder patients and control subjects are shown in figures 2-4. These are the mean values rounded to the nearest whole number for all the subjects in the sample including infusions where no RDC panic attack oc curred.…”
Section: Resultsmentioning
confidence: 99%
“…Psychophysiological measure ments were made continuously from 10 min before the intravenous line was placed until 10 min after it was removed. The results of the psychophysiological measurements are to reported separately [16]. Blood samples for biochemical studies were drawn through the heparin lock just before the infusion began, and at 10, 20, and 20-30 min after the infusion stopped.…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen in Table 11, an increase in resting heart rate and blood pressure in comparison to controls has been shown in some studies, but not others. One study showed significantly higher resting heart rate in panic disorder patients with yohimbine-induced panic attacks than healthy subjects (Charney et al, 1987a), although the same was not found for patients with lactate-induced panic attacks (Freedman et al, 1984). Resting heart rate was often measured during a period when the patients were anticipating a pharmacological challenge, which suggests that they may have been experiencing anticipatory anxiety.…”
Section: Noradrenergic Contributions Tomentioning
confidence: 99%
“…Patients with panic disorder have been found to have a decrease in peripheral lymphocyte p-adrenergic binding sites (B,,,=) and in increase in affinity (KD) (Brown et al, 19881, as well as a decrease in basal activity of cyclic adenosine monophosphate (CAMP), a second Refuting Nesse et al, 1984, 198513;Cameron and Nesse, 1988;Gorman et al, 1988;Freedman et al, 1984Gorman et al. 1988Charney et al, 1987aStein et al, 1992Woods et al, 1987Freedman et al, 1985;Taylor et al, 1986;Shear et al, 1987;Balon et al, 1988Balon et al, 1988White andBaker, Nesse et al, 1985b Nesse et al, 1984;Villacres et al, 1987 Cameron et al, 198413;Nesse et al, 1985aKO et al, 1983Brown et al, 1988Charney et al, 1990Cameron et al, 1990Cameron et al, 1984, 1990Albus et al, 1986 Charney et al, 1990a Uhde et al, 1984Uhde et al, , 1989Liebowitz et al, Uhde et al, 1986;Charney and 1981;Hoehn-Saric et al, 1981Heninger, 1986Curtis et al, 1989;Charney et al, 1992Charnev et al, 1984a, 1987a: Uhde Freedman et al, 1985Cameron et al, 1987;Villacres et al, 1987;Stein et al, 1992…”
Section: Noradrenergic Contributions Tomentioning
confidence: 99%